The design and validation of the sexual well-being model of Iranian men - Ghanbari, Kourosh; Mehrinejad, seyed Abolghasem; Sotodehasl, Nemat; Ghorbani, Raheb (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to design and validate the sexual well-being model of Iranian men. Methods: In terms of purpose, this research was applied-fundamental, in terms of the data type, it was mixed methods type (qualitative-quantitative) and exploratory, and in terms of data collection method, it was descriptive-correlational. The study population of the qualitative section of the study included academic experts and professionals in the field of sex therapy and sexual issues in Tehran that 17 people were selected as the sample size by using the purposive sampling method and saturation point. The quantitative section of the study included all married men over 25 years who were residents of Tehran in 2020 that 350 people were selected as the sample size by stepwise cluster sampling method. The data in this study were collected by library research method, semi-structured interview (for qualitative section), and a researcher-made questionnaire (for quantitative section). The experts confirmed the validity of the interview of the qualitative section. The results of the interview were coded in the qualitative section, and the research questions were examined by structural equation modeling and the one-sample t-test in the quantitative section. Results: The results of the analysis indicate that 22 main components can be identified out of 101 available items, of which seven main dimensions were extracted, including the quality of the sexual relationship, sexual attitude, sexual satisfaction, sexual intimacy, sexual self-schemas, sexual self-efficacy, and sexual dignity. The reliability of the dimensions of sexual well-being has been obtained by using Cronbach’s alpha as follows: 0.72 for the dimension of sex quality dimension, 0.76 for sexual attitude, 0.81 for sexual satisfaction, and 0.78 for sexual intimacy, 0.82 for sexual schemas, 0.80 for sexual self-efficacy, and 0.78 for sexual self-esteem. Also, the convergent validity of AVE> 0.5 and the divergent validity of CR> 0.7 were confirmed in this study. Conclusions: According to the results, it has been revealed that in terms of structural features, the Persian version of male sexual well-being is favorable and is a valid and reliable tool for measuring the sexual well-being of married men.